Glucosamine/β-Alanine Carbon Dots Use as DNA Carriers Into E. coli Cells - Devkota, Asmita; Pandey, Anju; Yadegari, Zeinab; Dumenyo, Korsi; Taheri, Ali (Frontiers in Nanotechnology, 2021)
Introducing foreign DNA into bacterial cells is essential in functional genomics and molecular research, and heat shock and electroporation are two major techniques of gene delivery in bacterial cells. However, both techniques are time and resource consuming and are limited to certain species or strains of bacteria. Hence, there is a need to develop new transformation alternatives and Carbon dots with unique features such as facile synthesis, ease of functionalization, non-toxicity, and biocompatibility are considered as novel biomolecule nanocarriers. In this study, we synthesized and evaluated DNA delivery potential of four carbon dots including: 1) amine coated carbon dots (NH2-FCDs); 2) carboxylate carbon dots (COOH-FCDs); 3) L-arginine and glucose carbon dots (N-CDs), and 4) citric acid and polyethyleneimine (PEI) carbon dots into Escherichia. Coli cells. We evaluated the minimum incubation time required for plasmid DNA delivery and the maximum plasmid size that can be delivered into E. coli cells using these CDs. Bacteria were incubated with carbon dot solution for different lengths of time and plated on selection media. Transformed colonies were counted using ImageJ online colony counting software and data were analyzed using R-software. Our study demonstrated that among all these CDs, only carboxylate carbon dots (COOH-FCDs) were able to deliver plasmid DNA into E. coli cells and the best incubation time was between 30-60 minutes. The maximum plasmid size that could be delivered was found to be 10 Kb and transformation efficiency decreased with larger plasmid size. transformation of E. coli using CDs is a novel technique?? that can be further studied in other bacterial strains or living cells.